Nonfatal Gun Use in Intimate Partner Violence: A Systematic Review of the Literature. (October 2018) - Sorenson, Susan B.; Schut, Rebecca A.
Guns figure prominently in the homicide of women by an intimate partner. Less is known, however, about their nonfatal use against an intimate partner. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we searched eight electronic databases and identified 10 original research articles that reported the prevalence of the nonfatal use of firearms against an intimate partner. Results indicate that (1) there is relatively little research on the subject of intimate partners' nonfatal gun use against women. (2) The number of U.S. women alive today who have had an intimate partner use a gun against them is substantial: About 4.5 million have had an intimate partner threaten them with a gun and nearly 1 million have been shot or shot at by an intimate partner. Whether nonfatal gun use is limited to the extreme form of abuse (battering) or whether it occurs in the context of situational violence remains to be seen. Regardless, when it comes to the likely psychological impact, it may be a distinction without a difference; because guns can be lethal quickly and with relatively little effort, displaying or threatening with a gun can create a context known as coercive control, which facilitates chronic and escalating abuse. Implications for policy, practice, and research are discussed, all of which include expanding an implicit focus on homicide to include an intimate partner's nonfatal use of a gun.